Highly Diastereoselective and Regioselective Copper‐Catalyzed Nitrosoformate Dearomatization Reaction under Aerobic‐Oxidation Conditions. Issue 14 (3rd March 2014) - Yang, Weibo; Huang, Long; Yu, Yang; Pflästerer, Daniel; Rominger, Frank; Hashmi, A. Stephen K.
Abstract An unprecedented copper‐catalyzed acylnitroso dearomatization reaction, which expands the traditional acylnitroso ene reaction and acylnitroso Diels–Alder reaction to a new type of transformation, has been developed under aerobic oxidation. Intermolecular and intra‐/intermolecular reaction modes demonstrate an entirely different N‐ or O‐acylnitroso selectivity. Hence, we can utilize this reaction as a highly diastereoselective access to a series of new pyrroloindoline derivatives, which are important structural motifs for natural‐product synthesis.